Challenges of Antiretroviral Therapy Among Children in Free State Province, South Africa - Olaleye, Abiola; Tsibolane, Yolisa; Van-Turha, Lydia; Monareng, Sibongile; Chikobvu, Perpetual; Boleme , Mohlouoa Sam; Serenata, Celicia (Scripta Medica, 2022)
Background/Aim: Antiretroviral therapy (ART) is an important intervention for survival among children in Sub Saharan Africa where HIV infection rates are comparatively high. Only few studies have explored issues relating to paediatric ART initiation and maintenance. This study was conducted to explore the perceptions and experiences of trained professional nurses regarding paediatric ART. Methods: Six focus group discussions (FGDs) were conducted among trained professional nurses in selected health facilities in Free State Province, South Africa. Verbatim transcripts were analysed with a thematic approach. Results: The participants of this study reported counselling as an important component of paediatric ART in health facilities. The problem of non-disclosure, migration, incomplete records from referral health facilities, inadequate health workforce and difficulty in record keeping were cited as barriers against paediatric ART. Conclusion: This study showed that initiation and adherence to antiretroviral therapy among eligible children faces a significant challenge.